Impact of twenty pesticides on soil carbon microbial functions and community composition. (November 2022) - Sim, Jowenna X.F.; Drigo, Barbara; Doolette, Casey L.; Vasileiadis, Sotirios; Karpouzas, Dimitrios G.; Lombi, Enzo
Abstract: Pesticides are known to affect non-targeted soil microorganisms. Still, studies comparing the effect of multiple pesticides on a wide range of microbial endpoints associated with carbon cycling are scarce. Here, we employed fluorescence enzymatic assay and real-time PCR to evaluate the effect of 20 commercial pesticides, applied at their recommended dose and five times their recommended dose, on soil carbon cycling related enzymatic activities (α-1, 4-glucosidase, β-1, 4-glucosidase, β-d -cellobiohydrolase and β-xylosidase), and on the absolute abundance of functional genes ( cbhl and chiA ), in three different South Australian agricultural soils. The effects on cellulolytic and chitinolytic microorganisms, and the total microbial community composition were determined using shotgun metagenomic sequencing in selected pesticide-treated and untreated samples. The application of insecticides significantly increased the cbhl and chiA genes absolute abundance in the acidic soil. At the community level, insecticide fipronil had the greatest stimulating effect on cellulolytic and chitinolytic microorganisms, followed by fungicide metalaxyl-M and insecticide imidacloprid. A shift towards a fungal dominated microbial community was observed in metalaxyl-M treated soil. Overall, our results suggest that the application of pesticides might affect the soil carbon cycle and may disrupt the formation of soil organic matter and structure stabilisation. Graphical abstract: Image 1 Highlights: Effects of 20 pesticides on carbon cycle related soil microbiota are investigated. Pesticide application stimulates cellulolytic and chitinolytic activities. Pesticide effects are influenced by both the pesticide class and soil properties. Insecticides significantly increase the abundance of microbial communities. Metalaxyl-M soil application shifts the microbial community towards fungi.